2012
DOI: 10.1038/bjc.2012.489
|View full text |Cite
|
Sign up to set email alerts
|

Primary cervical cancer screening with HPV testing compared with liquid-based cytology: results of round 1 of a randomised controlled trial – the HPV FOCAL Study

Abstract: Background:Round 1 data of human papillomavirus (HPV) FOCAL, a three-arm, randomised trial, which aims to establish the efficacy of HPV DNA testing as a primary screen for cervical cancer, are presented.Methods:The three arms are: Control arm – liquid based cytology with atypical squamous cells of unknown significance (ASC-US) triage with hrHPV testing; Intervention Arm – hrHPV at entry with liquid-based cytology (LBC) triage of hrHPV positives, with exit screen at 4 years; Safety check arm – hrHPV at entry wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 16 publications
3
77
0
Order By: Relevance
“…The lack of a correlation with histology and follow-up results is a limitation in the evaluation of the performance of the screening tests in that previous study (Swangvaree et al, 2010). The HC2-positive rate in LBC-negative women in the current study is within the reported range of 3.4-5.4% in other population-based studies in developed countries, which suggests that the performance of LBC in our study is comparable to that of the other studies Bulkmans et al, 2007;Castle et al, 2009;Ogilvie et al, 2012;Katki et al, 2013). The HC2-positive rate in LBC-negative women was reported as high as 11.2% in China (Zhao et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The lack of a correlation with histology and follow-up results is a limitation in the evaluation of the performance of the screening tests in that previous study (Swangvaree et al, 2010). The HC2-positive rate in LBC-negative women in the current study is within the reported range of 3.4-5.4% in other population-based studies in developed countries, which suggests that the performance of LBC in our study is comparable to that of the other studies Bulkmans et al, 2007;Castle et al, 2009;Ogilvie et al, 2012;Katki et al, 2013). The HC2-positive rate in LBC-negative women was reported as high as 11.2% in China (Zhao et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
“…Considering population-based studies in which HC2 testing was used, the HC2-positive prevalence of 7.1% in our study is comparable to the reported prevalence from countries in Europe and North America (6.3-8.1%) (Cuzick et al, 2003;Leinonen et al, 2008;Castle et al, 2009;Ogilvie et al, 2012;Zorzi et al, 2013), while it is higher than the prevalence in the Netherlands (4.5%) (Bulkmans et al, 2007) but is lower than that in India (10.3-16.2%) (Sankaranarayanan et al, 2009;Pandey et al, 2012;Rai et al, 2014) and China (9.9-27.5%) (Zhao et al, 2010;Li et al, 2013). Population-based studies for HPV detection by PCR techniques also have demonstrated high overall HPV prevalence in Latin America and Africa, where cervical cancer incidence is high (Herrero et al, 2000;Franceschi et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They consistently demonstrate an improved sensitivity of primary hrHPV screening for detecting cervical cancer precursor lesions (cervical intraepithelial neoplasia grades 2 and 3 (CIN2 and CIN3)) compared to cytology alone [5][6][7][8][9][10]. Some of these trials reported that primary hrHPV screening continues to have a sensitivity advantage over cytology after multiple rounds of screening.…”
Section: Introductionmentioning
confidence: 85%
“…Canadian randomized controlled trials 11,30 , and international knowledge syntheses 10,14,25,[31][32][33] also support this shift, which has been stressed in recent editorials 6,34,35 , yet some policy-makers feel that the cytology-based programs are "good enough," echoing the World Health Organization suggestion 36 . Researcher respondents were particularly adamant that Canadian cervical cancer screening programs should shift towards primary hpv testing because the increase in sensitivity has the greatest impact on population health and health system spending, in the era of hpv vaccination 6,37 .…”
Section: Discussionmentioning
confidence: 96%